Scaled quamtum mechanical (sqm) force field for amino-oxo tautomer of 1, 5 dimethylcytosine - Brandan, Silvia Antonia (2011)
We have performed a force field calculation for the amino-oxo tautomer of 1, 5- dimethylcytosine at B3LYP/6-31G* level following the refinement and the scaling methodologies. Quantum mechanical calculations were carried out by using Density Functional Theory (DFT/B3LYP) methods with 6-31G* basis set. The force constants were scaled using the transferable scale factors of Rauhut and Pulay. The refined force constants obtained in terms of independent symmetry coordinates have been expressed in terms of simple valence internal coordinates.